This is the house that Jack built - Adams, Pam. (New York : Child's Play (International) Ltd., 1977)
A cumulative nursery rhyme about the chain of events that started when Jack built a house. Features die-cut pages.
Keywords: Nursery rhymes; Toy and movable books -- Specimens; Children's poetry; Nursery rhymes; Toy and movable books; Nursery rhymes; Toy and movable books; Children's poetry